2012
DOI: 10.1063/1.4772635
|View full text |Cite|
|
Sign up to set email alerts
|

Mapping microwave field distributions via the spin Hall effect

Abstract: The spatial variation of the spin pumping–inverse spin Hall effect was studied in a palladium/permalloy bilayer via a coplanar waveguide ferromagnetic resonance (CPW-FMR) broadband technique. The inverse spin Hall signal is both inhomogeneous and asymmetric with respect to both the position along the CPW and the excitation port. Based on this observation, we show how the inverse spin Hall effect can be used as a sensitive probe for mapping the microwave magnetic field distribution in the FMR frequency range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…2, the precession angle θ can be directly estimated from the AMR voltage contribution assuming that the precession angle is uniform along the whole length and that the correlation between the rf field hrf from the CPW and the microwave current flowing in the bilayer is well established. However, it was recently shown that these assumptions do not hold [26], and, as will be shown, these assumptions can lead to large discrepancies in the estimates of the spin Hall angles when reversing the bilayer stacking order. In the limit of small precession angle θ =hrf cos(α)/ΔH (ΔH being the half linewidth at half !"…”
Section: Thickness Dependencementioning
confidence: 99%
See 2 more Smart Citations
“…2, the precession angle θ can be directly estimated from the AMR voltage contribution assuming that the precession angle is uniform along the whole length and that the correlation between the rf field hrf from the CPW and the microwave current flowing in the bilayer is well established. However, it was recently shown that these assumptions do not hold [26], and, as will be shown, these assumptions can lead to large discrepancies in the estimates of the spin Hall angles when reversing the bilayer stacking order. In the limit of small precession angle θ =hrf cos(α)/ΔH (ΔH being the half linewidth at half !"…”
Section: Thickness Dependencementioning
confidence: 99%
“…5(c), indicates that the SiO2/15Pd/15Py sample has a minimum microwave transmission at 8 GHz, whereas the power transmission remains fairly constant between 7 and 10 GHz for the SiO2/15Py/15Pd sample. This different behavior may reflect differences of impedance mismatch for different samples, which may result in varying standing--wave patterns for the microwaves in the samples [26]. Considering possible spatial inhomogeneities of the microwave field along the sample, calibrating the cone angle with the AMR--FMR method has the advantage that its dependence on the cone angle is identical to that obtained from the SHE voltage (see Eq.…”
Section: Calibration Of Precession Anglementioning
confidence: 99%
See 1 more Smart Citation
“…This geometry minimizes inductively coupled currents 27 that complicate the analysis of SHE measurements based on spin pumping. 14,15,28,29 Py(20 nm)/Pt(t Pt nm) bilayers (where the Pt thickness ranges from 0-10 nm) in the shape of a 20-lm  2-mm stripe were deposited on Si substrates with 300-nm-thick thermally grown SiO 2 . Four electrical leads for the electrically detected ferromagnetic resonance (FMR) are connected to the bilayer before integration with the coplanar wave-guide (CPW).…”
mentioning
confidence: 99%
“…Various approaches have been proposed based on different kinds of physical phenomena45678910111213. They often rely on scanning probe techniques with carefully designed scanning probes, particular materials and physical processes.…”
mentioning
confidence: 99%